Global warnings and the role of national filters in shaping formal governance of university performance - Bourmistrov, Anatoli; Haldma, Toomas; Kallio, Kirsi-Mari; Pettersen, Inger Johanne; Skoog, Matti (Emerald, 2025)
Purpose
The purpose of this article is to assess the continuing relevance of Olson et al.’s (1998) four primary concerns regarding the future development of New Public Financial Management (NPFM) in public service organizations. A particular focus is on understanding changes in the formal systems governing the performance management of universities across different “soft-NPFM” national contexts as well as the identification of successful strategies to mediate those four concerns.
Design/methodology/approach
Changes in the formal systems governing the performance management of universities in three European countries – Estonia, Finland and Norway – are reviewed in their historical contexts. Methodologically, this article is based on a content-driven analysis of documents, reports and scientific literature, supplemented by the collective memory of the co-authors.
Findings
“Warnings” have materialized quite differently in the three countries due to unique “national filters.” These filters are represented by different understandings of how universities are defined in terms of their governance and ownership, such as whether the universities are agents of the state or independent accounting entities with their own legal rights. These “national filters” seem to affect how NPFM is translated into the formal systems governing the performance management of universities.
Originality/value
This article contributes to the literature by examining how some countries and their governments manage to achieve “selective complementarity” of different reforms and trends. This complementarity helps to avoid the “dysfunctional effects” and “extremes” of NPFM.